Analysis of Children's Language Skills and Number Concepts through Technology in the Digital Era - Rosalianisa, Resi; Purwoko, Budi; Nurcahyati, Nur; Subrata, Heru (Journal of Educational Technology and Instruction, 2023)
Language is one of the elements behind the development of aspects of development that occur in early childhood, as well as a tool or means to communicate with other people and the environment. To develop and stimulate children's language development, they can carry out activities such as listening, speaking, reading, and writing, as well as saying and counting number symbols with digital-era devices. This study aims to describe language skills and recognize the concept of numbers in early childhood through technology. This research method is a literature study or review with a qualitative approach that collects data or is based on scientific writing, combining research with existing literature to solve problems. Collecting library data includes reading, storing, and managing research and concluding research materials. The research results show that developing language skills and recognizing numbers in early childhood requires listening, speaking, reading and writing, and calling and counting number symbols through technology. Keywords: language ability; number concept; technology